2012
DOI: 10.1093/nar/gks1326
|View full text |Cite
|
Sign up to set email alerts
|

Human LIGIV is synthetically lethal with the loss of Rad54B-dependent recombination and is required for certain chromosome fusion events induced by telomere dysfunction

Abstract: Classic non-homologous end joining (C-NHEJ) is the predominant DNA double-strand break repair pathway in humans. Although seven genes Ku70, Ku86, DNA-PKcs, Artemis, DNA Ligase IV (LIGIV), X-ray cross-complementing group 4 and XRCC4-like factor are required for C-NHEJ, several of them also have ancillary functions. For example, Ku70:Ku86 possesses an essential telomere maintenance activity. In contrast, LIGIV is believed to function exclusively in C-NHEJ. Moreover, a viable LIGIV-null human B-cell line and LIGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 100 publications
4
60
0
Order By: Relevance
“…We thus picked puromycin-resistant colonies derived from pHPRT2.2-Puro(−)-transfected cells and confirmed that correctly targeted clones are actually obtained (1 out of 127 clones in wild-type cells and 3 out of 45 clones in LIG4 -null cells) (Figure 3A). The increased targeting efficiency associated with LIG4 deficiency is consistent with previous studies using human cells [7], [28]. Of note, although pHPRT2.2-Puro(−) exhibited low targeting efficiencies compared to pHPRT8.9-Puro(-), gene-targeting enhancement associated with the LIG4 deficiency was more pronounced for pHPRT2.2-Puro(−) (∼10-fold increase) than for pHPRT8.9-Puro(−) (∼2–3-fold increase)(Figure 3A).…”
Section: Resultssupporting
confidence: 90%
“…We thus picked puromycin-resistant colonies derived from pHPRT2.2-Puro(−)-transfected cells and confirmed that correctly targeted clones are actually obtained (1 out of 127 clones in wild-type cells and 3 out of 45 clones in LIG4 -null cells) (Figure 3A). The increased targeting efficiency associated with LIG4 deficiency is consistent with previous studies using human cells [7], [28]. Of note, although pHPRT2.2-Puro(−) exhibited low targeting efficiencies compared to pHPRT8.9-Puro(-), gene-targeting enhancement associated with the LIG4 deficiency was more pronounced for pHPRT2.2-Puro(−) (∼10-fold increase) than for pHPRT8.9-Puro(−) (∼2–3-fold increase)(Figure 3A).…”
Section: Resultssupporting
confidence: 90%
“…From biochemical data based on the rejoining of a linear plasmid mediated by cellular extracts or purified proteins, we have proposed a double lock model against end joining at telomeric ends in which the TRF2/RAP1 complex inhibits C-NHEJ, whereas the DNA-PK complex blocks A-EJ [187]. This model was further substantiated and refined by data obtained in cells [63,84,188]. Several reports have characterized the first lock level, demonstrating that different shelterin components sustain different protective roles.…”
Section: A-ej and Telomeresmentioning
confidence: 90%
“…Biochemical studies in our lab have demonstrated that TRF2/RAP1 prevents proper Ku binding and DNA-PK activation at telomeric ends [187]. Thus, removal of TRF2 from telomeres provokes end-to-end chromosome fusions [195,196], which are mainly dependent on Lig4 activity [188,195,197,198]. Moreover, these C-NHEJ dependent end-fusions are completely abrogated in an ATM deficient background [190] and require the C-NHEJ facilitator 53BP1 [84].…”
Section: A-ej and Telomeresmentioning
confidence: 95%
See 1 more Smart Citation
“…To determine the relative contribution of C-(Ku-and LIG4-dependent) or A-(PARP1-and LIG3-mediated) NHEJ repair components to the telomere fusion events resulting from 17p TALEN activity, we performed parallel nucleofections into HCT116 cell lines deficient for individual (Oh et al 2013B Ruis, T Takasugi, S Oh, EA Hendrickson, in prep. ) and combined components (Supplemental Fig.…”
Section: High Resolution Mapping Of Inter-and Intra-chromosomal Recommentioning
confidence: 99%